A new algorithm for obstacle avoidance and tracing applied to wall painting robots - Liu, Xian-Ming (Journal of the Brazilian Society of Mechanical Sciences and Engineering, 2023)
This paper presents a new algorithm for the motion control of painting robots applied to intelligent motion control for wall painting and logistics handling. The study introduces a mathematical equation that can be described using a motion function. Its initial condition is around the obstacle point from the starting point to the target point, and its boundary condition is that a straight line or a line segment tangent to an arc in the search circle must be taken at the obstacle point. This mathematical equation is a nonlinear algebraic equation that finds the path from the starting point through the obstacle to the target point by a dynamic method. A minimum value evaluation criterion is applied to optimize multiple tracing paths to find an optimal solution. The advantage of this algorithm is that it simplifies the problem by finding the differences between them through a one-dimensional search for paths that avoid obstacles in the region of the motion function. It makes decisions by numerical comparison, thus avoiding the errors associated with objective evaluation. This algorithm can be applied in the field of intelligent control and the field of driverless vehicles. The combination of numerical and information control offers a new way of applying mathematical engineering in engineering control.